2003
DOI: 10.1097/01.sla.0000086660.35809.8a
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Nodal Stage Is an Independently Significant Predictor of Distant Failure in Patients With Squamous Cell Carcinoma of the Larynx

Abstract: Regardless of the index treatment modality, primary tumor site, or T stage, a higher clinical N stage at the time of presentation independently and significantly increases the risk of DM in patients with SCCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 27 publications
4
43
0
1
Order By: Relevance
“…However, the results are worse for local and regional control of advanced tumors (T3 and T4), especially if there are large lymph node metastases. 6 Goepfert et al 7 showed that the results of radiotherapy are similar to those of surgery for supraglottic lesions that can be removed with partial laryngectomy; ranging from 88.5% for T1 lesions to 60% for T4 lesions. The M.D.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results are worse for local and regional control of advanced tumors (T3 and T4), especially if there are large lymph node metastases. 6 Goepfert et al 7 showed that the results of radiotherapy are similar to those of surgery for supraglottic lesions that can be removed with partial laryngectomy; ranging from 88.5% for T1 lesions to 60% for T4 lesions. The M.D.…”
Section: Discussionmentioning
confidence: 99%
“…9 (13.84%) patients belonged to stage II and 7 24 Approximately 95% of all laryngeal and hypo pharyngeal malignant tumors are Squamous cell carcinoma. In this present series FNAC study show 89% positive finding (i.e., metastatic carcinoma).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we expect that induction chemotherapy with TPF (induction TPF) could reduce the risk of distant metastases and consequently lead to improved OS. Locally advanced HNSCC patients harboring diseases classified as nodal stage N2c, N3, or N2b with supraclavicular lymph node (LN) metastases are considered to have the greatest risk of distant metastases [11][12][13][14][15][16]. Thus, our institution has applied induction TPF followed by CRT for patients with a high risk of distant metastases since 2011.…”
mentioning
confidence: 98%